Práticas integrativas e complementares e saúde mental de estudantes universitários - Almeida, Ana Luiza Terra Grangeiro de (2023)
In recent years, research investigating the mental health of higher education students has increased. These studies have observed a high prevalence of mental health problems among university students, particularly in the areas of anxiety and depression. Scientific studies in various medical specialties have also demonstrated the benefits associated with the use of Integrative and Complementary Health Practices (ICHP) as an alternative or complementary approach to Allopathic Medicine, recognizing their therapeutic potential in terms of safety, cost-effectiveness, and acceptance. This present study aimed to investigate the ICHP used by university students and assess whether the use of these integrative practices impacts anxiety and/or depressive symptoms. It was a descriptive, observational, cross-sectional study conducted with students enrolled in public and private higher education institutions, using online questionnaires. The instruments employed were a sociodemographic questionnaire, a questionnaire regarding the use of ICHP, the Hospital Anxiety and Depression Scale (HADS), and the Depression Anxiety and Stress Scale-21 (DASS-21). Based on the participants' questionnaire responses, the data obtained aimed to establish a correlation between the use of ICHP and anxiety and depression symptoms. The sociodemographic profile of the 202 study participants revealed that 71.28% of the sample was aged between 18 and 25 years, 83.16% were female, and 69.30% were single. In terms of education, 74.25% were undergraduates, 17.32% were in postgraduate studies, and 8.41% already held a bachelor's degree. Regarding prior knowledge of ICHP, 56.43% of students reported having some knowledge, and 30.69% reported using some form of practice. However, 43.56% of students reported not being familiar with ICHP, and 69.30% reported not using them. The results obtained from the DASS-21 scale in both groups indicated mild depressive symptoms. In the domains of anxiety and stress, as well as in the results obtained from the HADS scale, higher scores were found in the group that utilizes ICHP. The results presented demonstrate that the use of Integrative and Complementary Health Practices did not lead to a reduction in the psychological parameters of the evaluated sample.